2015
DOI: 10.1007/s12560-015-9206-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Novel Virulent Phage of Lactobacillus casei ATCC 393

Abstract: A new virulent phage (Lcb) of Lactobacillus casei ATCC 393 was isolated from Chinese sauerkraut. It was specific to L. casei ATCC 393. Electron micrograph revealed that it had an icosahedral head (60.2 ± 0.8 nm in diameter) and a long tail (251 ± 2.6 nm). It belonged to the Siphoviridae family. The genome of phage Lcb was estimated to be approximately 40 kb and did not contain cohesive ends. One-step growth kinetics of its lytic development revealed latent and burst periods of 75 and 45 min, respectively, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…In our previous work, a virulent phage against L. casei ATCC 393 was isolated from fermented vegetables and designated as Lcb [ 40 ]. The phage Lcb was purified and stored in our laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, a virulent phage against L. casei ATCC 393 was isolated from fermented vegetables and designated as Lcb [ 40 ]. The phage Lcb was purified and stored in our laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…The deposit was then resuspended in SM (sodium-magnesium-buffered saline) buffer. Phage DNA was extracted by phenol–chloroform–isoamyl alcohol and then precipitated by isopropanol [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…These studies demonstrated, as discussed for phages infective to other LAB genera, traditional pasteurization treatments (LTLT, 63 °C for 30 min and HTST, 72 °C for 15 s) would be not enough to reach complete inactivation of dairy phages, since most of them survive (in diverse levels) at these conditions. However, no phage particles were detected at 90 °C for 5 min, except for some phages infective to Lactobacillus delbrueckii [32,38] and Lactobacillus casei / paracasei [58,59], which keep their infectivity until 30 min at this temperature (depending on the phage). On the other hand, phages infecting lactobacilli showed diverse responses (phage-dependent behavior) when they were subjected to treatments at 63 and 72 °C for 45–60 min.…”
Section: Efficiency Of Thermal and Chemical Treatments On The Inacmentioning
confidence: 99%
“…On the other hand, a lower thermal resistance was observed for a non-dairy phage (Lcb), isolated from Chinese sauerkraut when its thermal resistance was studied in MRS broth (Biokar, Beauvais, France). In this way, treatments at 70 °C for 30 min or at 80 °C for 10 min were enough to inactivate the entire phage particle population [38] (Table 4). As mentioned for St. thermophilus phages, those infective of Lb.…”
Section: Efficiency Of Thermal and Chemical Treatments On The Inacmentioning
confidence: 99%
“…Most bacteriophages act optimally at temperatures between 30 -50˚C (Bao et al, 2015;Ji et al, 2015;Zhang et al, 2015). Bacteriophages were also found to be active over the temperature range of 4-50˚C (Jun et al, 2013) and 4-60˚C (Easwaran et al, 2015) for Shigella flexneri phage pSf-1 and Escherichia coli phage Sw1, respectively.…”
Section: Properties Of Bacteriophagesmentioning
confidence: 99%